Finite element analysis of reinforced concrete beam with two circular opening at constant moment area by using ansys software - Bong, Kit Hian (2014)
Beam is one of the most important structural element for a building because it can withstanding primarily load by resisting bending. Thus, there is a need to have a proper design so that it have enough strength to be sustain loading acting on it. Here the study was conducted a beam with two circular web opening at constant moment area with the beam dimension 200 x 400 x 3000 mm. In order to analyse these beam, ANSYS software was been used in these study although there are still many existing commercial engineering software such as STAAD PRO, LUSAS, MATLAB and etc. This is because ANSYS is an engineering stimulation software which offer stimulation solution set that a design process requires. Besides, it is widely used in industry to stimulate the response of a physical system to structural loading. By using ANSYS software, it can help to analyse complex structure without simplify the structure and also help to analyse the reaction force, deformation, deflection and axial stress as well as obtain the maximum deflection. With this study, the finding seem has been fulfil to the objectives where the results of simulation of Reinforce concrete beams with two web opening such as maximum deflection, stresses and strains has been analysed with respect to six random inputs suchas force, reinforcement diameter, link diameter, stirrups diameter and spacing